Genetic potential of two Brazilian maize races for breeding purposes. II. Plant characters - Santos, Manoel Xavier dos; Filho, José Branco de Miranda; Junior, Cláudio Lopes de Souza (Pesquisa Agropecuaria Brasileira, 2014)
The genetic potential of the Brazilian maize races Cravo and Entrelaçado was evaluated with special attention on plant height (PH), ear height (EH) and number of tassel branches (NTB). After the initial cross of each race with the improved and adapted variety ESALQ-PB 1 (E), the adapted x exotic populations Cravo x ESALQ-PB 1 (EC) and Entrelaçado x ESALQ-PB 1 (EE) were recombined twice. A total of 196 half sib families of each recombined population were seleeted for experimental evaluations with the objective of measuring the effect of the introgression on the average yield and the yield potential of EC and EE populations in relation to the adapted E population. The benefits resulting from gene introgression of the Cravo race were verified since PH, EH and NTB means of the semi-exotic EC population were lower than those of the adapted population, while these benefits for the semi-exotic EE population were not verified. Values found for the estimates of genetic parameters showed that for the three characters studied, substantial gains are possible to obtain, using simple seleetion schemes.